Small Scale Splint and Veneer Industries of Kerala State, India: A Technical Efficiency Analysis - Gopakumar, S.; Devi, P. Indira; Kunhikannan, C. (Indian Forester, 2013)
Using the stochastic production frontier approach, the technical efficiency of splint and veneer industry of Kerala was analysed. Ailanthus triphysa, Bombax ceiba and Melicope lunu-ankenda (Gaertn.) are still the main raw material species. But the demand of rubber wood as an alternate raw material is now rising. The mean technical efficiency (TE) of this sector was only 0.6. This paper discusses the social and other industrial reasons for the low efficiency in this sector. A migrant, unskilled workforce is possibly bringing down the efficiency. Coupled with this, the employment of obsolete techniques and technologies are the main reasons identified for the low TE scores. However, there many industries within this cluster which had high individual TE scores. This reinforces the scope for improvement within this industry. The marked presence of educated, young entrepreneurs is a definite indication of this industry's continued potential to provide sustainable livelihoods in the future.